CORRUPTION, TRANSPARENCY, AND REPUTATION: THE ROLE OF PUBLICITY IN REGULATING POLITICAL DONATIONS. (3rd May 2016) - Rowbottom, Jacob
Abstract: This article looks at the public disclosure of political donations as a case study to examine the role of transparency in addressing concerns about undue influence and corruption. The article will explore three issues. The first is to understand what it means to say that a political donation is corrupt. There is considerable disagreement on the ethics of political fundraising and this article will show how public opinion has a role in setting the standards expected of politicians. The second issue is what role the public disclosure of political donations plays in deterring and detecting corruption. While the disclosure requirements were introduced to promote greater trust in politics, it will be argued that increases in transparency have fed a growing culture of mistrust. The logic of the transparency requirements also requires the free public discussion of particular political donations and related ethical issues. The third issue is how that process of free discussion can come into tension with rights to privacy and reputation. The article will explore how the attempts to reconcile the different areas of law both reflect and shape the political culture.